2015
DOI: 10.1680/macr.14.00259
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of residual tensile strength of fire-damaged concrete using a non-linear resonance vibration method

Abstract: The non-linear resonance vibration method is a promising non-linear acoustic technique that has been used to evaluate contact-type defects of concrete induced by exposure to fire. In this work, an experimental study was performed on thin fire-damaged concrete discs to evaluate residual tensile strength using the non-linear resonance vibration method. Using correlation analysis, an experimental relationship is proposed between splitting tensile strength and a hysteretic non-linearity parameter (HNP), as measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Among these factors, it has been reported that the after-fire curing period insignificantly affects the residual material properties under an air-cured condition, while firedamaged concrete under a completely saturated curing condition appears to recover its mechanical strength (Park et al 2015). Accordingly, for a correlation analysis, the concrete samples in this study were air-cured after heating to ignore the curing condition.…”
Section: Sample Preparation: Fire-damaged Concretementioning
confidence: 97%
See 3 more Smart Citations
“…Among these factors, it has been reported that the after-fire curing period insignificantly affects the residual material properties under an air-cured condition, while firedamaged concrete under a completely saturated curing condition appears to recover its mechanical strength (Park et al 2015). Accordingly, for a correlation analysis, the concrete samples in this study were air-cured after heating to ignore the curing condition.…”
Section: Sample Preparation: Fire-damaged Concretementioning
confidence: 97%
“…Linear ultrasonic methods, which measure wave velocity, wave attenuation, and impact echo, are conventional ultrasonic methods and have been widely used to evaluate damaged concrete, particularly firedamaged concrete (Chaix et al 2003;Colombo and Felicetti 2007;Dilek and Leming 2007;Epasto et al 2010;Kee and Nam 2015;Yang et al 2009). However, these linear methods exhibit lower sensitivity to distributed defects and contacttype defects at the micro-scale (Jhang 2009;Park et al 2015) compared to nonlinear ultrasonic methods, which are more sensitive to early-stage micro-scale defects as these defects cause nonlinear behavior of an incident wave (Zaitsev et al 2006). To investigate this phenomenon in concrete, Chen et al (2010) performed an experiment to characterize microscale defects induced by an alkali-silica reaction by using a nonlinear impact resonance acoustic spectroscopy technique.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior can be investigated using different nonlinear resonant techniques whose basic principle is to excite the materials at their resonance frequencies at different strain amplitudes. For concretelike materials, previous studies reported that the nonlinear behavior shows enhanced sensitivity to detect alkali-silica reaction, 29 thermal damage, 30,31 and freezing-thawing damage, 32 when compared with the standard values of the dynamic modulus or relative modulus of elasticity. The present paper evaluates the variation of the linear and nonlinear dynamic properties upon carbonation of mortar samples, using resonant vibration data obtained according to the standard ASTM C215-14.…”
Section: Introductionmentioning
confidence: 99%